2015
DOI: 10.1093/bioinformatics/btv043
|View full text |Cite
|
Sign up to set email alerts
|

CypRules: a rule-based P450 inhibition prediction server

Abstract: CypRules is freely accessible at http://cyprules.cmdm.tw/ and models, descriptor and program files for all compounds are publically available at http://cyprules.cmdm.tw/sources/sources.rar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The classifiers were trained on data from the PubChem Bioassay 1851 dataset (Veith et al., ) using 50 molecular and physicochemical descriptors. CypRules (Shao et al., ) is another web service that predicts inhibitors and non‐inhibitors of the same major CYPs based on the same data. It utilizes decision trees in combination with the concept of information entropy.…”
Section: Methods For Cyp Specificity Predictionmentioning
confidence: 99%
“…The classifiers were trained on data from the PubChem Bioassay 1851 dataset (Veith et al., ) using 50 molecular and physicochemical descriptors. CypRules (Shao et al., ) is another web service that predicts inhibitors and non‐inhibitors of the same major CYPs based on the same data. It utilizes decision trees in combination with the concept of information entropy.…”
Section: Methods For Cyp Specificity Predictionmentioning
confidence: 99%
“…Generally, to probe the molecular basis of CYP450 related metabolism, inhibition and drug–drug interaction potential a number of ligand-, structure-based and integrated modeling studies have been reported in literature [18,19,20,21,22,23,24,25]. Particularly, to gain deeper insights into the binding of ligands to CYP3A4, various in silico studies based on quantitative structure–activity relationships (QSAR), pharmacophore models and machine learning methods have been undertaken [26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…However, these in silico platforms have not been used to prospectively identify and biologically test new inhibitors. One of these platforms, CypRules 6 , is publicly available.…”
Section: Discussionmentioning
confidence: 99%